2012
DOI: 10.3109/15376516.2012.718811
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress: a possible mechanism for lead-induced apoptosis and nephrotoxicity

Abstract: Lead-induced nephrotoxicity is a human health hazard problem. In this study, Human mesangial cells (HMCs) were treated with different concentration of lead acetate (5, 10, 20 μmol/l) in order to investigate the oxidative stress and apoptotic changes. It was revealed that lead acetate could induce a progressive loss in HMCs viability together with a significant increase in the number of apoptotic cells using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl tetrazolium (MTT) assay and flow cytometry, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Regarding the occupationally exposed populations, experimental studies have asserted that higher BLLs are associated with an increase in MDA or TBARS concentrations (Sandhir et al 1994 ;Kaczmarek-Wdowiak et al 2004 ;Jia et al 2012 ). All the studies that enrolled workers exposed to lead reported elevated levels of LPO products, except for 2 studies that did not identify a statistical signifi cance associated with higher BLLs (Table 4 ).…”
Section: Types and Utility Of Biomarkersmentioning
confidence: 89%
See 1 more Smart Citation
“…Regarding the occupationally exposed populations, experimental studies have asserted that higher BLLs are associated with an increase in MDA or TBARS concentrations (Sandhir et al 1994 ;Kaczmarek-Wdowiak et al 2004 ;Jia et al 2012 ). All the studies that enrolled workers exposed to lead reported elevated levels of LPO products, except for 2 studies that did not identify a statistical signifi cance associated with higher BLLs (Table 4 ).…”
Section: Types and Utility Of Biomarkersmentioning
confidence: 89%
“…Lead-induced OS by ROS generation also represents a mechanism underlying lead neurotoxicity (Verstraeten et al 2008 ). Jia et al ( 2012 ) observed that lead promoted OS in the human mesangial cells, which can be an important mechanism underlying lead-induced nephrotoxicity. Moreover, lead has been proven to affect numerous systems throughout the body, including the hormonal, immune, and gastrointestinal systems, at different blood lead levels (BLLs) (EPA 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 The fluorescent imaging analysis using Hoechst and TOPRO-3 to assess nuclear morphology and cell membrane integrity revealed that despite the toxicity of lead, PZT nanoparticles showed no changes in either parameter suggesting that cell viability was maintained after exposure. 35 In the case of yeast cells, surface absorbed nanoparticles tend to damage the cell wall leading to the inhibition of cell proliferation and cell death and these responses are closely related with the nanoparticle size. 34 The mechanism of lead-based nanoparticles-induced cell death is traditionally apoptotic, via oxidative stress resulting in a decrease in mitochondrial activity inducing apoptosome formation.…”
Section: Bnt-bt and Pzt Nanoparticle Exposure Does Not Exert Cytotoximentioning
confidence: 99%
“…Some studies have confirmed the possible involvement of reactive oxygen species (ROS) in lead-induced toxicity. 3,[5][6][7] Any compound that induces oxidative stress does so by accelerating the generation of pro-oxidants and at the same time may also reduce cellular antioxidant defenses. Studies have reported that exposure to lead will lead to the disruption of the reducing status of a tissue and drive ROS formation, which will damage essential biomolecules such as proteins, lipids, and DNA.…”
Section: Introductionmentioning
confidence: 99%